Preparation method of negative titanium tab of lithium titanate battery and prepared titanium tab
By ultrasonic cleaning and multi-step surface treatment of titanium metal, and combining it with the titanium ear glue through hot pressing process, the negative electrode of lithium titanium electrode of lithium titanate battery was prepared, solving the oxidation reaction of aluminum and nickel ears in the prior art and The problem of poor welding performance has achieved efficient conductivity, corrosion resistance and stability of titanium electrodes.
Patent Information
- Application Number
- CN202411431854.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-07
AI Technical Summary
Among the existing lithium titanate batteries, the positive electrode ears are mostly aluminum ears and nickel ears, which have problems with oxidation reactions and poor welding performance at high voltages, resulting in battery liquid leakage and gas surges.
The negative electrode titanium electrode ear is prepared by using titanium metal. The surface treatment is treated with ultrasonic cleaning, acidification liquid pickling, passivation liquid passivation and sealing agent sealing, and the PET film and double-sided adhesive are fixed with the ear ear gel, and the hot pressing process is used to make Extreme ear glue is combined with titanium metal belt.
The good conductivity, corrosion resistance and mechanical strength of the titanium electrode ear are achieved, the volume changes of the battery during charging and discharging are avoided, and the circulation performance and service life of the battery are improved.
Abstract
Description
Technical Field
[0001] The present disclosure relates to a method for preparing a negative electrode titanium pole ear of a lithium titanate battery and the prepared titanium pole ear, and relates to H01M, and specifically to the field of battery electrode connection. Background Art
[0002] Lithium titanate batteries use lithium titanate as the positive electrode active material. Because its spinel structure is a three-dimensional lithium ion diffusion channel, lithium titanate batteries have excellent power activity and high and low temperature resistance. At present, the positive electrode tabs in lithium titanate batteries are mostly aluminum tabs, and the negative electrode tabs are mostly nickel tabs. The conductivity of aluminum and nickel tabs is good, but there is a risk of oxidation reaction under high voltage, generating metal ion dissolution. The welding performance of aluminum and nickel is also poor. During battery packaging and later processing, the tab glue and tab metal may break, causing battery leakage and gas bloating. Although aluminum tabs will form an oxide film in the electrolyte to prevent aluminum oxidation and dissolution, the aluminum oxide film will break during the use of the battery, resulting in aluminum oxidation and dissolution. Therefore, it is very important to develop a metal tab that is resistant to electrolyte corrosion, conductive, and has excellent welding performance.
[0003] Chinese invention patent CN114552133B discloses a method for preparing a negative pole ear with an inert metal coating on the surface and a lithium battery. The present invention coats the pole ear with an inert metal layer, which can avoid the corrosion of the pole ear by the electrolyte and improve the durability and reliability of the battery. However, the electroplating of the inert metal is costly and the process is complicated. Chinese invention patent CN201810611441.3 discloses a method for preparing a lithium battery pole ear. By removing the passivation film layer between adjacent glue areas, the welding performance of the metal sheet is improved, the internal resistance of the lithium battery is reduced, and the stability of the lithium battery pole ear welding in the subsequent lithium battery production process is ensured; and the reliability of the bonding between the pole ear glue and the passivation film is not affected. However, the new passivation film formed after the passivation film layer is removed will break during the use of the battery, and there is a risk of oxidation and dissolution of the pole ear metal. Summary of the invention
[0004] In order to develop a metal pole ear that is resistant to electrolyte corrosion, conductive, and has excellent welding performance, the first aspect of the present disclosure provides a method for preparing a negative electrode titanium pole ear of a lithium titanate battery, comprising the following steps:
[0005] S1 cuts the titanium metal strip into sections, then ultrasonically cleans it to remove oil, impurities, rinses it and dries it;
[0006] S2 performs surface treatment on titanium belt;
[0007] S3 uses PET film and double-sided tape to fix the treated titanium metal strip and the lug glue;
[0008] S4 uses a hot pressing process to combine the lug glue with the titanium metal strip;
[0009] S5 cooling, cutting, getting.
[0010] As an optional embodiment, degreasing powder is used during the ultrasonic cleaning, and the concentration of the degreasing powder is 40-60 g / L. Optionally, the concentration of the degreasing powder is 45-55 g / L; further optionally, the concentration of the degreasing powder is 50 g / L.
[0011] As an optional implementation, the ultrasonic cleaning temperature in step S1 is 40-50° C., and the cleaning time is 50-70 seconds.
[0012] As an optional implementation, the ultrasonic cleaning temperature in step S1 is 45° C. and the cleaning time is 60 s.
[0013] As an optional implementation, the surface treatment includes pickling with an acidizing solution, passivation with a passivating solution, and sealing with a sealing agent.
[0014] As an optional implementation, the surface treatment specifically includes: pickling with acidizing liquid at room temperature for 5-10s, rinsing with pure water and drying; passivation treatment with passivation liquid at 20-40℃ for 30-60s, rinsing with pure water and drying; sealing treatment with sealing agent at 30-50℃ for 20-40s, rinsing with pure water and drying.
[0015] As an optional implementation, the surface treatment specifically includes: pickling with acidizing liquid at room temperature for 7-9 seconds, rinsing with pure water and drying; passivation treatment with passivation liquid at 25-35℃ for 35-55 seconds, rinsing with pure water and drying; sealing treatment with sealing agent at 35-45℃ for 25-35 seconds, rinsing with pure water and drying.
[0016] As an optional implementation, the surface treatment specifically includes: pickling with acidizing solution at room temperature for 8 seconds, rinsing with pure water and drying; passivation treatment with passivation solution at 30°C for 45 seconds, rinsing with pure water and drying; sealing treatment with sealing agent at 40°C for 30 seconds, rinsing with pure water and drying.
[0017] As an optional implementation, the acidifying liquid is an aqueous solution of an acidic substance, and the acidic substance includes at least one of hydrochloric acid, hydrofluoric acid, nitric acid, and periodic acid.
[0018] As an optional implementation manner, the concentration of the hydrochloric acid is 30-40wt%, and the concentration of the hydrofluoric acid is 30-50wt%.
[0019] As an optional implementation manner, the concentration of the hydrochloric acid is 36 wt %, and the concentration of the hydrofluoric acid is 40 wt %.
[0020] As an optional implementation, the volume ratio of hydrofluoric acid to hydrochloric acid in the acidifying solution is (1-2): (2-8).
[0021] As an optional implementation manner, the volume fraction of the hydrofluoric acid in the acidizing liquid is 1-2%; the volume fraction of the hydrochloric acid in the acidizing liquid is 2-8%.
[0022] As an optional implementation manner, the volume fraction of the hydrofluoric acid in the acidizing liquid is 1.3-1.8%; the volume fraction of the hydrochloric acid in the acidizing liquid is 3-7%.
[0023] As an optional implementation manner, the volume fraction of the hydrofluoric acid in the acidizing liquid is 1.5%; the volume fraction of the hydrochloric acid in the acidizing liquid is 5%.
[0024] As an optional embodiment, the passivation solution includes 15-50 g / L hydrated sulfate, 2-5 g / L tungstate, 2-5 g / L dibasic alkyl acid, 5-10 g / L anhydrous sulfate, 0.1-0.5 g / L anionic surfactant, and water.
[0025] As an optional embodiment, the passivation solution includes 30-40 g / L hydrated sulfate, 3-4 g / L tungstate, 3-4 g / L dibasic alkyl acid, 6-8 g / L anhydrous sulfate, 0.2-0.4 g / L anionic surfactant, and water.
[0026] As an optional embodiment, the passivation solution includes 33 g / L hydrated sulfate, 3.5 g / L tungstate, 3.5 g / L dibasic alkyl acid, 7 g / L anhydrous sulfate, 0.3 g / L anionic surfactant, and water.
[0027] As an optional embodiment, the anhydrous sulfate includes at least one of anhydrous nickel sulfate, anhydrous aluminum sulfate, anhydrous potassium sulfate, anhydrous barium sulfate, and anhydrous sodium sulfate.
[0028] As an optional embodiment, the anhydrous sulfate is nickel sulfate.
[0029] As an optional implementation, the hydrated sulfate is chromium sulfate hexahydrate; the dibasic alkyl acid is oxalic acid, and the anionic surfactant is sodium dodecyl sulfate.
[0030] As an optional implementation, the tungstate is sodium tungstate.
[0031] As an optional implementation, the pH value of the passivation solution is 1-3, and the pH value of the sealing agent is 8-10.
[0032] As an optional implementation, the pH value of the passivation solution is 2, and the pH value of the sealing agent is 9.
[0033] As an optional implementation, the sealing agent is an aqueous solution of fluorozirconate, and the volume concentration of the fluorozirconate is 5-15%.
[0034] As an optional implementation, the sealing agent is an aqueous solution of potassium fluorozirconate, and the pH value needs to be adjusted to 8-10 with sodium hydroxide.
[0035] As an optional implementation, in step S4, the hot pressing temperature is 140-170° C., the hot pressing time is 40-60 s, and the hot pressing pressure is 0.2-0.4 MPa.
[0036] As an optional implementation manner, the hot pressing in step S4 is: 145° C., 0.2 MPa for 40 s; 155° C., 0.3 MPa for 50 s; 165° C., 0.4 MPa for 60 s.
[0037] A second aspect of the present disclosure provides a negative electrode titanium tab for a lithium titanate battery, which is prepared using the above-mentioned preparation method.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] (1) The method for preparing the negative electrode titanium tab of the lithium titanate battery disclosed in the present invention uses metallic titanium as the tab metal, which has good conductivity, corrosion resistance and mechanical strength, and does not undergo volume changes during the battery charging and discharging process, thereby improving the battery's cycle performance and service life.
[0040] (2) The method for preparing the negative electrode titanium tab of the lithium titanate battery disclosed in the present invention is to acid-wash the titanium metal strip and then passivate it, which can not only improve the peel strength between the tab metal and the tab glue, but also will not affect the corrosion resistance of the titanium tab.
[0041] (3) The preparation method of the negative electrode titanium ear of the lithium titanate battery disclosed in the present invention uses a passivation solution containing tungstate to form an insulating oxide film on the surface of the titanium ear, thereby improving the conductivity without sacrificing the corrosion resistance of the titanium ear, and achieving the goal that after being immersed in the electrolyte, it is not easy to corrode, has good conductivity, and has high peel strength.
[0042] (4) In the method for preparing the negative electrode titanium tab of the lithium titanate battery disclosed in the present invention, hydrofluoric acid and hydrochloric acid are used in a volume ratio of (1-2): (2-8) as the acidifying solution for acidification treatment, and the resulting activation effect is good and corrosion-resistant, and can be used in lithium titanate batteries with high current density.
[0043] (5) The titanium anode ear of a lithium titanate battery prepared by the preparation method disclosed in the present invention can be safely used in a wide temperature range, especially can maintain good performance in a low temperature environment. The titanium material and the lithium titanate anode material have similar potentials, which can reduce the polarization and internal resistance of the battery and improve the efficiency and power of the battery. DETAILED DESCRIPTION
[0044] Example 1
[0045] A method for preparing a negative electrode titanium tab of a lithium titanate battery, characterized in that it comprises the following steps:
[0046] S1 cuts the titanium metal strip 2 into sections, then ultrasonically cleans and removes oil, impurities, rinses and dries;
[0047] S2 performs surface treatment on the titanium metal strip 2;
[0048] S3 fixes the treated titanium metal strip 2 and the tab glue 1 with a PET film and double-sided adhesive tape;
[0049] S4 combines the tab glue 1 with the titanium metal strip 2 through a hot pressing process;
[0050] S5 is naturally cooled to 25°C and cut into pieces.
[0051] The PET film was purchased from Shanghai Yunnuo Packaging Materials Co., Ltd., with a size of 140 mm*100 mm*0.05 mm;
[0052] The double-sided tape was purchased from Shanghai Yunnuo Packaging Materials Co., Ltd. and has a size of 3 mm.
[0053] Degreasing powder is used during the ultrasonic cleaning, and the concentration of the degreasing powder is 50g / L;
[0054] The degreasing powder was purchased from Hubei Andeng Environmental Protection Technology Co., Ltd. with a brand name of D19.
[0055] In step S1, the ultrasonic cleaning temperature is 45° C. and the cleaning time is 60 seconds.
[0056] The surface treatment specifically includes: pickling with acidizing liquid at room temperature for 8s, rinsing with pure water and drying; passivation treatment with passivation liquid at 30°C for 45s, rinsing with pure water and drying; sealing treatment with sealing agent at 40°C for 30s, rinsing with pure water and drying, the rinsing time is 10s, the drying temperature is 100°C, and the drying time is 20s.
[0057] The acidifying liquid is an aqueous solution of hydrochloric acid and hydrofluoric acid, the concentration of the hydrochloric acid is 36 wt %, and the concentration of the hydrofluoric acid is 40 wt %.
[0058] The volume fraction of the hydrofluoric acid in the acidizing liquid is 1.5%; the volume fraction of the hydrochloric acid in the acidizing liquid is 5%.
[0059] The passivation solution includes 33 g / L of hydrated sulfate, 3.5 g / L of tungstate, 3.5 g / L of dibasic alkyl acid, 7 g / L of anhydrous sulfate, 0.3 g / L of anionic surfactant, and water.
[0060] The anhydrous sulfate is nickel sulfate.
[0061] The hydrated sulfate is chromium sulfate hexahydrate; the dibasic alkyl acid is oxalic acid, and the anionic surfactant is sodium dodecyl sulfate.
[0062] The tungstate is sodium tungstate.
[0063] The passivation treatment is to add the titanium metal strip into the passivation tank, use the MMO anode, and perform passivation at a passivation current density of 10A.
[0064] The sealing agent is a potassium fluorozirconate aqueous solution, the pH of which is adjusted to 9 with sodium hydroxide, and the volume concentration of the potassium fluorozirconate is 10%.
[0065] The pH value of the passivation solution is 2.
[0066] The hot pressing conditions in step S4 are: 155° C., 0.3 MPa, hot pressing for 50 seconds.
[0068] Example 2
[0069] A method for preparing a negative electrode titanium tab of a lithium titanate battery, the specific implementation method is the same as that of Example 1, except that the volume fraction of the hydrochloric acid in the acidifying solution is 20%.
[0070] The passivation solution includes 33 g / L of hydrated sulfate, 35 g / L of aluminum sulfate, 3.5 g / L of dibasic alkyl acid, 7 g / L of anhydrous sulfate, 0.3 g / L of anionic surfactant, and water.
[0071] The anhydrous sulfate is nickel sulfate.
[0072] The hydrated sulfate is chromium sulfate hexahydrate; the dibasic alkyl acid is oxalic acid, and the anionic surfactant is sodium dodecyl sulfate.
[0073] Example 3
[0074] A method for preparing a negative electrode titanium tab of a lithium titanate battery, the specific implementation method is the same as that of Example 1, except that the volume fraction of the hydrochloric acid in the acidifying solution is 15%.
[0075] The passivation solution includes 33 g / L of hydrated sulfate, 4 g / L of aluminum sulfate, 3.5 g / L of dibasic alkyl acid, 7 g / L of anhydrous sulfate, 0.3 g / L of anionic surfactant, and water.
[0076] The anhydrous sulfate is nickel sulfate.
[0077] The hydrated sulfate is chromium sulfate hexahydrate; the dibasic alkyl acid is oxalic acid, and the anionic surfactant is sodium dodecyl sulfate.
[0078] Performance Testing
[0079] The negative electrode titanium tabs of the lithium titanate battery prepared in Examples 1-3 were immersed in an electrolyte at a temperature of 85°C, a concentration of 1000ppm after adding water to the electrolyte, and an immersion time of 24 hours to observe the corrosion of the tabs. The tab glue peel strength was then tested using a tensile tester (peeling angle 180°, peeling speed 175mm / min, peeling ambient temperature 25°C).
[0080] The test results are shown in Table 1.
[0081] Table 1
[0082] Corrosion resistance Peel strength (N / mm) Example 1 No corrosion on lugs 1.9 Example 2 The ear is corroded 0.8 Example 3 The ear is corroded 1.3
Claims
1. A method for preparing a negative electrode titanium tab of a lithium titanate battery, characterized in that: The following steps are involved: S1 cuts the titanium metal strip into sections, then ultrasonically cleans it to remove oil, impurities, rinses it and dries it; S2 performs surface treatment on titanium belt; S3 uses PET film and double-sided tape to fix the treated titanium metal strip and the lug glue; S4 uses a hot pressing process to combine the lug glue with the titanium metal strip; S5 cooling, cutting, getting.
2. The method for preparing the negative electrode titanium tab of a lithium titanate battery according to claim 1, characterized in that: The surface treatment includes pickling with an acidizing solution, passivation with a passivating solution and sealing with a sealing agent.
3. The method for preparing the negative electrode titanium tab of a lithium titanate battery according to claim 2, characterized in that: The surface treatment specifically includes: pickling with acidizing solution at room temperature for 5-10s, rinsing with pure water and drying; passivation treatment with passivation solution at 20-40°C for 30-60s, rinsing with pure water and drying; sealing treatment with sealing agent at 30-50°C for 20-40s, rinsing with pure water and drying.
4. The method for preparing the negative electrode titanium tab of a lithium titanate battery according to claim 2, characterized in that: The acidifying liquid is an aqueous solution of an acidic substance, and the acidic substance includes at least one of hydrochloric acid, hydrofluoric acid, nitric acid, and periodic acid.
5. The method for preparing the negative electrode titanium tab of a lithium titanate battery according to claim 3, characterized in that: The volume ratio of hydrofluoric acid to hydrochloric acid in the acidifying solution is (1-2):(2-8).
6. The method for preparing the negative electrode titanium tab of a lithium titanate battery according to claim 2, characterized in that: The passivation solution comprises 15-50 g / L of hydrated sulfate, 2-5 g / L of tungstate, 2-5 g / L of dibasic alkyl acid, 5-10 g / L of anhydrous sulfate, 0.1-0.5 g / L of anionic surfactant and water.
7. The method for preparing the negative electrode titanium tab of a lithium titanate battery according to claim 6, characterized in that: The anhydrous sulfate includes at least one of anhydrous nickel sulfate, anhydrous aluminum sulfate, anhydrous potassium sulfate, anhydrous barium sulfate, and anhydrous sodium sulfate.
8. The method for preparing the negative electrode titanium tab of a lithium titanate battery according to claim 2, characterized in that: The pH value of the passivation solution is 1-3, and the pH value of the sealing agent is 8-10.
9. The method for preparing the negative electrode titanium tab of a lithium titanate battery according to claim 2, characterized in that: The sealing agent is a fluorozirconate aqueous solution, and the volume concentration of the fluorozirconate is 5-15%.
10. A negative electrode titanium tab for a lithium titanate battery, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of lithium battery tab
CN108878758A
A method for preparing a negative electrode tab with an inert metal coating and a lithium battery
CN114552133B